Hollow Organosilica Nanoparticles for Drug Delivery. Issue 37 (5th October 2018) - Rahmani, Saher; Akrout, Alia; Budimir, Jelena; Aggad, Dina; Daurat, Morgane; Godefroy, Anastasia; Nguyen, Christophe; Largot, Hanene; Gary‐Bobo, Magali; Raehm, Laurence; Durand, Jean‐Olivier; Charnay, Clarence
Abstract: The sol‐gel synthesis of hollow organosilica nanoparticles incorporating amino groups with uniform size are described. These nanoparticles were successfully prepared via a microemulsion method. Then, the hollow nanoparticles were loaded with gemcitabine hydrochloride or methotrexate and studied in MCF‐7 breast cancer cells. Abstract : Hollow Organosilica Nanoparticles (HONPs) with uniform size and incorporating amino groups were achieved via a microemulsion method. These hollow nanoparticles displayed a large cavity, enabling drug loading and release. In particular, the hydrophilic gemcitabine was loaded without early release and no chemical coupling was required. HONPs loaded with gemcitabine were very efficient to be internalized by cancer cells and to induce MCF‐7 cell killing.